Analysis and simulation of catamaran mini houseboat design by using Computational Fluid Dynamic (CFD) / Muhammad Danish Irfan Mohd Aihsan - Mohd Aihsan, Muhammad Danish Irfan (2024)
Investigation of the effect of wave-induced motions on the performance and stability modification Mini houseboat, including the motions, total resistance, and water slamming. So, this project is about the design of Two-In-One-Mini Houseboat that might be suitable to be use for personal user for recreational. The mini houseboat can be used as a closed houseboat and can be use as open boat. The objective in this research is Computational Fluid Dynamics (CFD) simulation is to analyse fluid flow around the hull of the mini houseboat design and analyse the velocity, drag force, air resistance and water resistance to improve the performance of the design. The CFD simulation will be using the software ANSYS to visualize the simulation result. The result by doing the CFD on the project design will be more accurate and valid to be use on the design because software can calculate critical parameters and detect every algorithm with the simulation analyse design capabilities and performance. So, if the designed mini houseboat unbalances the simulation will show it. The reliability of the result from the CFD simulation to visualize the fluid flow and optimize the data for the velocity, resistance, drag force on the mini houseboat design to ensure the design suitable, safe, and worthwhile according to its purpose.